A novel ER-targeted two-photon fluorescent probe for monitoring abnormal concentrations of HClO in diabetic mice. Issue 36 (26th August 2021) - Zhang, Weiyao; Song, Wenhui; Lin, Weiying
Abstract : Diabetes is closely related to the presence of excess HClO induced by endoplasmic reticulum stress. Abstract : Diabetes is closely related to the presence of excess HClO induced by endoplasmic reticulum stress. Thus, a novel two-photon fluorescent probe was designed and synthesized for the detection of HClO in the endoplasmic reticulum. Significantly, it has been verified that high glucose can indeed induce oxidative stress of the endoplasmic reticulum and produce excessive HClO. Moreover, the probe has also been successfully used in tissue imaging of diabetic mice.